A Bibliometric Study of Spiral Curriculum Research: Intellectual Structure and Future Directions - Loso Judijanto (Eastasouth Institute, 2026)
This study aims to map the intellectual structure, thematic evolution, and future research directions of spiral curriculum research through a bibliometric approach. Data were collected from a reputable database and analyzed using VOSviewer to examine co-occurrence networks, temporal trends, and research density. The findings reveal that spiral curriculum research is characterized by strong interdisciplinary connections, with dominant clusters emerging in medical education, general curriculum and learning sciences, and engineering education. The network analysis indicates that spiral curriculum functions as a central pedagogical framework closely associated with key concepts such as teaching, learning, and curriculum design. The overlay visualization shows a clear temporal shift from early applications in technical and engineering domains toward broader educational theory and, more recently, toward applied and competency-based contexts, particularly in medical education. Furthermore, the density analysis highlights that while core themes are well-established, emerging areas such as motivation, decision-making, and technology-enhanced learning remain underdeveloped. These findings suggest that spiral curriculum research is transitioning toward more integrative and outcome-oriented approaches. This study contributes to the literature by providing a comprehensive knowledge map of spiral curriculum research and identifying potential avenues for future investigation, particularly in digital learning integration and interdisciplinary applications.